2006
DOI: 10.1016/j.bandc.2005.11.005
|View full text |Cite
|
Sign up to set email alerts
|

What aspects of face processing are impaired in developmental prosopagnosia?

Abstract: What aspects of face processing are impaired in developmental prosopagnosia?Le Grand, R.; Cooper, P.A.; Mondloch, C.J.; Lewis, T.L.; Sagiv, M.; de Gelder, Bea; Maurer, D. Published in: Brain and Cognition Document version:Publisher's PDF, also known as Version of record Publication date: 2006Link to publication Citation for published version (APA):Le Grand, R., Cooper, P. A., Mondloch, C. J., Lewis, T. L., Sagiv, M., de Gelder, B., & Maurer, D. (2006). What aspects of face processing are impaired in developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
205
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(239 citation statements)
references
References 90 publications
28
205
3
Order By: Relevance
“…For some prosopagnosic cases, the N170 did not show the characteristic increased amplitude for faces as compared with objects (28-31), whereas for other cases an increase of the N170 for faces relative to objects was reported much as in normal subjects (31,32). This lack of consistency may be related to the heterogeneous nature of developmental disorders like prosopagnosia and is in line with mixed results obtained in behavioral (9,20,33) and functional MRI studies (34)(35)(36), mostly of single patients.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…For some prosopagnosic cases, the N170 did not show the characteristic increased amplitude for faces as compared with objects (28-31), whereas for other cases an increase of the N170 for faces relative to objects was reported much as in normal subjects (31,32). This lack of consistency may be related to the heterogeneous nature of developmental disorders like prosopagnosia and is in line with mixed results obtained in behavioral (9,20,33) and functional MRI studies (34)(35)(36), mostly of single patients.…”
mentioning
confidence: 59%
“…When prosopagnosia occurs in normal adults as a consequence of brain damage, it is most often associated with lesions in the occipito-temporal brain regions (1)(2)(3)(4)(5)(6). In other cases, there is no evidence of brain damage, and the exact etiology of face recognition deficits is unknown (7)(8)(9). The pattern of deficits in acquired and developmental prosopagnosia is similar as far as some basic aspects of face processing are concerned (10).…”
mentioning
confidence: 99%
“…The processing of facial attractiveness in prosopagnosic subjects has recently been investigated in subjects with congenital prosopagnosia (Sadr et al, 2004, Le Grand et al, 2006, with results that have led to mixed conclusions. One group suggested that the processing of facial attractiveness could be dissociated from the processing of facial identity (Sadr et al, 2004), while the other group concluded that impaired face perception negatively affects the development of the "tools" needed for aesthetic judgments during an early critical period (Geldart et al, 1999, Cooper and Maurer, 2002, Le Grand et al, 2006.…”
Section: Discussionmentioning
confidence: 99%
“…To test this possibility, we examined participants' ability to (1) integrate local elements into a global form (Fig. 1 D), and (2) to integrate local motion cues to produce a percept of global motion (Le Grand et al, 2006) (Fig. 1 E).…”
Section: Roi Hemispherementioning
confidence: 99%